Pengaruh Kondisi Keuangan Perusahaan, Ukuran Perusahaan, dan Audit Client Tenure Terhadap Opini Audit Going Concern - Fanny Khamillah Hasim; Tutty Nuryati; Uswatun Khasanah (Jurnal Ilmiah Wahana Pendidikan, 2023)
This study examines the financial condition of companies, company size, and tenure of audit clients. These will affect the going concern audit report. Building on previous research, this study aims to strengthen relationships or influences between variables. The purpose of writing this article is to hypothesize the effects between variables for further study. The results of this literature review article are his three hypotheses: 1) An entity's financial condition affects the audit opinion on going concern; 2) Company size impacts going concern reporting; 3) Audits of tenured clients influence the opinion of going concern audits